Time for a paradigm shift toward a restorative culture - Cross, Adam; Nevill, Paul; Dixon, Kingsley; Aronson, James (WILEY, 2019)
The United Nations' recent declaration of a Decade on Ecosystem Restoration (2021–2030) conveys the immense scales of degradation we face and the urgency of ecological recovery. Yet it speaks predominantly to productivity-based approaches that may poorly balance conservation and development goals. As a result, it overlooks or distorts the very real potential for the holistic restoration of natural and cultural ecosystems to achieve lasting social and human health and well-being benefits, and help stem the grotesque loss of biodiversity and ecosystem health in these times. There is need for a profound paradigm shift to address the prevailing economic and political climate that is keeping our world and biosphere on their current ominous trajectory. Such a paradigm shift could be based on the idea of a “restorative culture.” Practically, this could proceed by coupling the foundational philosophies and modus operandi of restoration ecology with public health medicine. The outcome would be an era of more healthy and more science- and knowledge-driven sustainable restoration and local redevelopment. A restorative culture would recognize the fundamental linkages between ecosystems and human health, and consider biodiversity as fundamental to personal, community, and cultural well-being and resilience. This requires public–private and community and individual partnerships at city, township, and watershed scales, as well as progressive industry champions working in collaboration with governments and the United Nations.